A Praça André de Albuquerque, Natal/RN, na visão de seus frequentadores - Sousa, Bernardete de Lourdes Queiroga de (2006)
The study offers a global and interpretative view of the person-environment inter-action at André de Albuquerque Plaza, in Natal, RN, according to a descriptive-exploratory approach that aimed at learning about the space converted into place, as it is perceived and experienced by users, who attribute meaning to it. The main objective was to critically analyze the relationship person-plaza, based on data collected about users perception, utilization and ascribed meaning. I have employed an Environmental Psychology multi-method approach, including informal observations, interactive poster session, videotaping and interviews. The results indicated that the plaza, besides being a passage point, is also a spot of urban convergence for several groups, particularly taxi drivers, flanelinhas, skate boarders and students. In regard to the perception of the place, an overall positive evaluation of the plaza was verified, since people perceive selectively what interests them. In terms of usage, different groups of users presented diverse patterns of utilization, also observed in the attributed meanings. The plaza is a work place for taxi drivers and flanelinhas and a sports arena for the skate boarders, with a practical meaning for both groups. For students and other users it is a place for meeting and leisure, revealing a stronger affective quality, responsible for feelings of well being, tranquility and relaxation. The data so obtained could contribute for future government projects of intervention in those spaces, aiming at its preservation as an open spot among the concrete of city buildings, offering better quality of life, not only for today, but also for future generations